On the Reuse and Maintenance of Aspect-Oriented Software: An Assessment Framework - Sant’Anna, Cláudio; Garcia, Alessandro; Chavez, Christina; Lucena, Carlos; von Staa, Arndt (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2003)
Aspect-oriented software development (AOSD) is gaining wide attention both in research environments and in industry. Aspect-oriented systems encompass new software engineering abstractions and different complexity dimensions. As a consequence, AOSD poses new problems to empirical software engineering. It requires new assessment frameworks specifically tailored to measure the reusability and maintainability degrees of aspect-oriented systems. This paper presents an assessment framework for AOSD, which is composed of two components: a suite of metrics and a quality model. These components are based on well-known principles and existing metrics in order to avoid the reinvention of well-tested solutions. The proposed framework has been evaluated in the context of two different empirical studies with different characteristics, diverse domains, varying control levels and different complexity degrees. Based on empirical and quantitative analysis, the advantages and drawbacks of the framework components are discussed.